2019
DOI: 10.11606/issn.2317-0190.v26i4a168380
|View full text |Cite
|
Sign up to set email alerts
|

Efeito em curto prazo de dois protocolos de hidrocinesioterapia em crianças com síndrome congênita associada à infecção do vírus Zika

Abstract: Objetivo: Avaliar o efeito em curto prazo de dois protocolos de hidrocinesioterapia sobre o tônus muscular e o nível de estresse de crianças com SCZ. Métodos: Estudo cruzado, randomizado e cego, com crianças com microcefalia/SCZ entre 3-36 meses de idade. O tônus foi avaliado pela Escala Modificada de Tardieu(EMT), analisando-se o grau de tônus muscular e a amplitude de movimento articular(ADM); o nível de estresse, através de Escala visual analógica de faces variando desde um estado sem estresse (1) até estre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 27 publications
(30 reference statements)
3
2
0
Order By: Relevance
“…In addition, Silva et al 16 showed gains in muscle tone and socialization with the environment by involving the family of children with microcephaly in a carnival activity that included colors and textures, different tastes and temperatures, a decorated environment, and different positions as forms of stimulation. This finding corroborates the study by Monteiro et al, 20 who used the aquatic environment as a means of stimulation for children diagnosed with CZVS and showed a reduction in muscle tone and improvement in range of motion. It is important to note that the study by Monteiro et al 20 was the only randomized clinical trial that met the eligibility criteria established in this systematic review.…”
Section: Judgement Lowsupporting
confidence: 92%
See 4 more Smart Citations
“…In addition, Silva et al 16 showed gains in muscle tone and socialization with the environment by involving the family of children with microcephaly in a carnival activity that included colors and textures, different tastes and temperatures, a decorated environment, and different positions as forms of stimulation. This finding corroborates the study by Monteiro et al, 20 who used the aquatic environment as a means of stimulation for children diagnosed with CZVS and showed a reduction in muscle tone and improvement in range of motion. It is important to note that the study by Monteiro et al 20 was the only randomized clinical trial that met the eligibility criteria established in this systematic review.…”
Section: Judgement Lowsupporting
confidence: 92%
“…This finding corroborates the study by Monteiro et al, 20 who used the aquatic environment as a means of stimulation for children diagnosed with CZVS and showed a reduction in muscle tone and improvement in range of motion. It is important to note that the study by Monteiro et al 20 was the only randomized clinical trial that met the eligibility criteria established in this systematic review.…”
Section: Judgement Lowsupporting
confidence: 92%
See 3 more Smart Citations